The influence of nutrition on patients with digestive diseases - AMBROSE, LENUTA; POPA, ANDREEA; ILIE, LACRAMIOARA; BALTA, ALEXIA ANASTASIA; FOTACHE, PAULA ALINA; MORARU, DANA-IULIA; MAFTEI, NICOLETA-MARICICA; MEHEDINTI, MIHAELA CEZARINA (Technium BioChemMed, 2023)
Abstract. Maintaining health, improving the quality of life is largely related to the way of eating and the quality of food consumption. The way of eating is a central life issue, because apart from the very important social activities and other recreational activities, man still has three meals daily. Diet and nutrition are of paramount importance in disease prevention and health promotion. In fact, a slight imbalance in the quantitative and/or qualitative consumption of food can and does have long-term effects on health. In order to determine how nutrition influences the lifestyle of people suffering from digestive diseases, a retrospective study was conducted at the Municipal Hospital, St. Ierah Dr. Luca,, Onești during the period 1.01.2015-31.03.2020. In this study, 1019 patients with digestive pathology (gastric ulcer, duodenal ulcer, acute haemorrhagic gastritis, gastritis, gastroduodenitis) were included. As indicated by the research, it was found that the 1019 tested patients were diagnosed with ulcers, gastritis and gastro-duodenitis. According to the research, we can conclude that improper eating habits are risk factors in triggering, maintaining, or aggravating digestive pathology.